Discovery of a potent cyclooxygenase-2 inhibitor, S4, through docking-based pharmacophore screening, in vivo and in vitro estimations. Issue 8 (6th June 2016) - Tseng, Tien-Sheng; Chuang, Show-Mei; Hsiao, Nai-Wan; Chen, Yi-Wen; Lee, Yu-Ching; Lin, Chi-Chen; Huang, Cheng; Tsai, Keng-Chang
Abstract : Cyclooxygenase (COX; EC: 1.14.99.1), the key enzyme in prostaglandin production in the human body, is a major pharmacological target for developing anti-inflammatory agents. Abstract : Cyclooxygenase (COX; EC: 1.14.99.1), the key enzyme in prostaglandin production in the human body, is a major pharmacological target for developing anti-inflammatory agents. Nonsteroidal anti-inflammatory drugs exhibit anti-inflammatory and analgesic activities when inhibiting COX-2 but cause gastrointestinal toxicity and other side effects because of concurrent inhibition of COX-1. Thus, potent and safe inhibitors against COX-2 are urgently required. We constructed a novel docking-based pharmacophore model for screening selective COX-2 inhibitors and discovered compoundsS1, S2, S3, andS4, which apparently inhibit COX-2. Particularly, S4 inhibits COX-2 in vitro and shows a potent anti-inflammatory effect in vivo without cytotoxicity. Molecular docking analyses revealed thatS4 interacted satisfactorily with the active site of COX-2 but not with that of COX-1. This reveals thatS4 more specifically inhibits COX-2 and has potential for application in developing anti-inflammatory and anticancer agents.